THE ROLE OF WEB RESOURCES IN FORMATION OF THE FUTURE ENGLISH TEACHERS’ PROFESSIONAL COMPETENCE (American Journal of Pedagogical and Educational Research, 2024)
The article discusses the value of educational web resources for future English teachers, aiming to enhance their professional competence in the information society. It explores the concept of competence in foreign literature and analyzes the teacher’s professional competence. Challenges in teaching a foreign language using Internet technologies are considered, along with examples of web resources like Hotlist and Web Quest. Recommendations suggest using these resources for foreign language training to develop logical thinking, creativity, and communication skills. The formation of future English teachers’ competence with web resources is theoretically proven and experimentally tested.